Analysis of perceived stress, coping resources and life satisfaction among students at a newly established institution of higher learning - Mudhovozi, P (South African Journal of Higher Education, 2011)
A survey was conducted to analyse perceived stress, coping resources and life satisfaction among university students at an institution of higher learning. Seventy-three students randomly selected from third year Social Sciences class participated in the study. A self-report questionnaire was administered to the participants. The results showed that stress was pervasive among university students. The main factors that affected the students were personal problems, academic problems, relationships and environmental problems. Students mainly relied on emotion-focused and avoidance-oriented coping strategies. They were moderately satisfied with life at university. Future research with a more representative sample should be conducted to get generalisable findings.